Detecion y evaluacion de beta-exotoxina(s) en caldo de cultivo de bacillus thuringiensis (Berliner) - Carreras, B.=700 1 Barquin, J.R.; Ricardo, C.
(Es, En)
Ilus., 16 ref.
Keywords: BACILLUS THURINGIENSIS; EXOTOXINAS; ENSAYO; CUBA